Methods in behavioral research - Cozby, Paul. (Boston McGraw-Hill Higher Education, 2015)
Methods in Behavioral Research has achieved its market-leading position with its concise and strategic approach to methodological decision making. Combining helpful pedagogy and rich examples, Cozby's eleventh edition again incorporates learning objectives, illustrative graphics, and activities to increase student involvement. Highlights of the new edition include a broader introduction of different research techniques in Chapter 4, extensive revision of the ?validity of measurements? section, and updated structural equations models.
Includes bibliographical references (p. 381-392) and index.
Keywords: Psychology -Research -Methodology.